The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.2139/ssrn.437620
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Hypothetical Bias in Stated Preference Valuation

Abstract: A meta-analysis of hypothetical bias in stated preference valuation" (2005 Abstract. Individuals are widely believed to overstate their economic valuation of a good by a factor of two or three. This paper reports the results of a meta-analysis of hypothetical bias in 28 stated preference valuation studies that report monetary willingness-to-pay and used the same mechanism for eliciting both hypothetical and actual values. The papers generated 83 observations with a median ratio of hypothetical to actual value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
377
5
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 290 publications
(400 citation statements)
references
References 44 publications
11
377
5
7
Order By: Relevance
“…Assessing the external validity of WTP estimates was beyond the scope of this review, whilst the external validity of WTP estimates have been robustly assessed in three systematic reviews and meta-analyses since 2004 [35][36][37]. In addition, included studies must have been able to define participants' choice sets in the real world, implicitly limiting the scope of this review to predictions of choices within choice sets which can be represented consistently in a stable manner across real-world and hypothetical tasks, e.g., uptake of a test, but not adherence to a treatment over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing the external validity of WTP estimates was beyond the scope of this review, whilst the external validity of WTP estimates have been robustly assessed in three systematic reviews and meta-analyses since 2004 [35][36][37]. In addition, included studies must have been able to define participants' choice sets in the real world, implicitly limiting the scope of this review to predictions of choices within choice sets which can be represented consistently in a stable manner across real-world and hypothetical tasks, e.g., uptake of a test, but not adherence to a treatment over time.…”
Section: Discussionmentioning
confidence: 99%
“…The external validity of WTP estimates has been explored fully and recently in the literature, and we therefore do not include WTP studies in this review. This work explores the external validity of willingness-to-pay estimates from contingent valuations and conjoint analyses, mostly in transport fields [32][33][34], including three meta-analyses [35][36][37]. These studies conclude that hypothetical bias can be substantial, with median bias levels ranging from 25 to 300%.…”
Section: Background On Validity In Dcesmentioning
confidence: 99%
“…List and Gallet 2001 found that willingness-to-pay studies have a lower bias than those that estimate willingness-to-accept, and that to some extent this bias may vary across elicitation mechanisms. Murphy, et al 2005 note that the number of willingness-to-accept studies is quite small and List and Gallet's result is sensitive to the outcomes of a single study. Similarly, many elicitation mechanisms in List and Gallet have only a single study so their conclusions about elicitation mechanisms should be interpreted with caution.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence that these hypothetical values exceed actual payments (List and Gallet 2001;Murphy, et al 2005;Harrison and Rutström, forthcoming). In recognition of this hypothetical bias problem, the NOAA guidelines state that CV value estimates should be halved unless responses can be calibrated (Arrow, et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation